Java Plum (Syzygium cumini (L.) Skeels) Leaf Extract Lowers Serum Urea Levels in Lead-Acetate-Induced Rats - Amriza, Muhammad Zidan; Rita, Rauza Sukma; Sy, Elmatris (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2022)
Lead is a hazardous metal to living things. Lead can cause oxidative stress in the body, inhibit enzyme activity, damage nucleic acids, and prevent DNA repair, resulting in cell death. Java plum (Syzygium cumini (L.) Skeels) leaves are rich with antioxidants. The research aimed to evaluate if Java plum leaf extract affected serum urea levels in lead acetate-induced rats. This study is an experimental study using 24 male rats with a randomized post-test only control group design. Rats were divided into three groups: the group that did not get any treatment, namely the negative control (NC); the group that was given lead acetate (40 mg/kg BW) was a positive control (PC); and the group that was given lead acetate (40 mg/kg BW) and Java plum leaf extract (150 mg/kg BW) was the treatment group (T), using an oral probe. The treatment was carried out for four weeks. After four weeks, the rats were killed, and their serum urea levels were examined using the urease-GLDH: enzymatic UV test method. The results showed the mean serum urea levels in the NC, PC, and T groups were 17.87±2.18, 22.79±2.52, and 18.12±2.19 mg/dl, respectively. There were significant differences in all groups (p-value < 0.05) in the one-way Anova. Additionally, the post hoc Tukey HSD test demonstrated a statistically significant difference between the positive control and treatment groups as well as between the negative and positive control groups (p-value < 0.05). The conclusion was that Java plum leaf extract was able to reduce serum urea levels under lead intoxication conditions.